Designing an AI-Based Expert System to Enhance Standard Language Use on Social Media - Aini, Qurotul; Naurah, Syahla; Bist, Ankur Singh; Sunarjo, Richard Andre; Novitasari, Dewiana; Sasono, Ipang; Apriliasari, Dwi (International Transactions on Artificial Intelligence, 2025)
The widespread use of social media has significantly transformed the way people communicate, often leading to informal, shortened, and mixed-language expressions that deviate from standard linguistic norms. This phenomenon raises concerns about the erosion of proper language usage, particularly among younger generations. This study aims to design an AI-based expert system to support and improve the use of standard Indonesian on digital communication platforms. By integrating language rules into a decision-support model, the system can provide real-time feedback on grammar, spelling, and appropriate word usage during online interactions. This research adopts a qualitative approach through literature review and system design framework, emphasizing the need for intelligent linguistic assistance tools. The proposed expert system will be capable of analyzing user-generated content, detecting deviations from formal language standards, and offering suggestions or corrections. The findings contribute to ongoing efforts to preserve national language identity in the digital age and promote linguistic awareness through technology. Ultimately, this study offers an innovative solution to bridge the gap between informal digital trends and the preservation of standard language, encouraging responsible and high-quality communication in the modern digital ecosystem.